Risk factors for failed induction of labor: A retrospective study in a single, tertiary, perinatal-care center - Maika Nariai; Osamu Wada-Hiraike; Takayuki Iriyama; Takahiro Seyama; Keiichi Kumasawa; Yasushi Hirota; Yutaka Osuga (Taiwanese Journal of Obstetrics & Gynecology, 2025)
Objective: To estimate the incidence and associated risk factors of failed induction of labor (IOL). Materials and methods: A retrospective, case–control study was conducted on a cohort of women who underwent IOL from January 2020 to December 2023 and delivered after 34 weeks of gestation at our hospital (n = 1541). Failed IOL was defined as delivering with a cesarean section for any reason. The control group consisted of successful vaginal deliveries, including forceps and vacuum deliveries after IOL. Both primiparous and multiparous women were included in the study. We identified associated risk factors of failed IOL via multivariable logistic regression analysis. Results: During the study period, 1541 of 4244 women (36.3 %) who delivered at our hospital underwent IOL. Among them, 326 women had a failed IOL, an estimated incidence of 21.2 % (95 % confidence interval [CI]: 19.1 %–23.3 %). The multivariable analysis revealed that older age (adjusted odds ratio [aOR] = 1.07 for each 1-year increase, 95 % CI: 1.04–1.11, P < 0.001), primiparity (aOR = 0.24 95 % CI: 0.16–0.35, P < 0.001), conception by using assisted reproductive technology (aOR = 1.45 95 % CI: 1.06–2.00, P = 0.021) larger birth weight (aOR = 1.05 for each 100 g increase, 95 % CI: 1.01–1.65, P = 0.023), hypertensive disorders of pregnancy (HDPs) (aOR = 2.53, 95 % CI: 1.80–3.56, P < 0.001), the lower simplified Bishop score before induction (aOR = 0.70 for each 1-point increase, 95 % CI: 0.61–0.80 P < 0.001), and the use of no epidural anesthesia (aOR = 0.42, 95 % CI: 0.31–0.57, P < 0.001) were independently associated with failed IOL. Conclusions: Age, primiparity, method of conception, birth weight, HDPs, and simplified Bishop score should be considered as the predictor of failed IOL.